Multiscale Remote Sensing Data Integration for Gully Erosion Monitoring in Southern Brazil: Case Study - Fábio Marcelo Breunig; Malva Andrea Mancuso; Ana Clara Amalia Coimbra; Leonardo José Cordeiro Santos; Tais Cristina Hempe; Elaine de Cacia de Lima Frick; Edenilson Roberto do Nascimento; Tony Vinicius Moreira Sampaio; William Gaida; Elias Fernando Berra; Romário Trentin; Arsalan Ahmed Othman; et al. (AgriEngineering, 2025)
The degradation and loss of arable soils pose significant challenges to global food security, requiring advanced mapping and monitoring techniques to improve soil and crop management. This study evaluates the integration of Unmanned Aerial Vehicles (UAVs) and orbital sensor data for monitoring and quantifying gullies with low-cost data. The research focuses on a gully in southern Brazil, utilizing high-spatial-resolution imagery to analyze its evolution over a 25-year period (2000–2024). Photointerpretation and manual delineation procedures were adopted to define gully shoulder lines, based on low-cost and multiple-spatial-resolution data from Google Earth Pro (GEP), UAVs and conventional aerial photographs. Planimetric, volumetric, climatic, and pedological parameters were assessed and evaluated over time. Field inspections supported our interpretations. The results show that gully expansion can be effectively mapped and monitored by combining high-spatial-resolution GEP data with aerial imagery. The gully area has increased by more than 50% over the past two decades, based on GEP data, which were corroborated by submeter-resolution UAV data. The findings indicate that the erosive process remains active, progressing toward the base level. These results provide critical insights for land managers, policymakers, and agricultural stakeholders to implement targeted soil recovery strategies and mitigate further land degradation.